Glass Ceiling dalam Peningkatan Jenjang Karir Pegawai Negeri Sipil Perempuan di Lingkungan Pemerintah Kota Medan - Wahyuni Sari Nasution; R Ira Irawati; Didin Muhafidin (JANE - Jurnal Administrasi Negara, 2022)
This research is about Glass Ceiling in Advancing Career Paths for Female Civil Servants in Medan City Government motivated by the trend of increasing the number of female civil servants occurring both nationally and in the city of Medan itself, where in the city of Medan alone the number of female civil servants is almost double the total male civil servants. However, the dominance of women in terms of the number of female civil servants both at the national and regional levels has not been reflected in the level of participation of female civil servants in structural positions. Most women occupy Echelon IV structural positions and the higher the structural positions, the fewer women occupy these positions, this phenomenon can be assumed that the career development of female civil servants in high structural positions is relatively slower than male civil servants and the obstacles are invisible. that hinders career advancement is called Glass Ceiling.This study was conducted to identify the factors causing the glass ceiling in increasing the career path of Female Civil Servants in the Medan City Government and to obtain new inputs as policy implications in order to further reduce the factor glass ceiling thereby increasing the participation of female civil servants in structural positions. In reviewing this, the author uses three approaches, Women's Sex Role, Gender Stereotype and Work Environment. The author conducted in-depth interviews with 10 informants from six agencies within the Medan City Government. Then to process the data obtained, the author conducted an analysis using the six stages of Cresswell.The results show that Women's Sex Role, Gender Stereotype and Work Environment are factors that influence the increase in Career  Paths of Female Civil Servants in the Medan City Government. So to overcome this and increase the participation of female civil servants in structural positions the policy implications are designing gender-sensitive infrastructure, increasing the involvement of women in public positions and policies and improving policies related to ASN in the implementation of the merit system, especially in terms of promotion. Penelitian ini mengenai Glass Ceiling dalam Peningkatan Jenjang Karir Pegawai Negeri Sipil Perempuan di Lingkungan Pemerintah Kota Medan yang dilatar belakangi  oleh tren peningkatan jumlah PNS Perempuan terjadi baik di nasional maupun Kota Medan sendiri, dimana di Kota Medan sendiri jumlah PNS Perempuan hamper dua kali lipat dari total PNS Laki-Laki. Namun dominasi Perempuan dari segi jumlah PNS Perempuan baik ditingkat nasional hingga daerah belum tercermin dalam tingkat partisipasi PNS Perempuan dalam jabatan Struktural. Perempuan paling banyak menempati pada jabatan struktural Eselon IV dan semakin tinggi jabatan struktural maka makin sedikit perempuan yang menempati posisi tersebut, fenomena ini dapat diasumsikan bahwa perkembangan karir PNS Perempuan pada jabatan struktural tinggi relatif lebih lambat dibandingkan dengan PNS laki-laki dan hambatan yang tidak terlihat yang menghambat peningkatan jenjang karir disebut Glass Ceiling. Penelitian ini dilakukan untuk mengidentifikasi faktor penyebab glass ceiling dalam peningkatan jenjang karir Pegawai Negeri Sipil Perempuan di Lingkungan Pemerintah Kota Medan dan mendapatkan masukan baru sebagai implikasi kebijakan agar selanjutnya mampu mengurangi faktor glass ceiling tersebut sehingga meningkatkan partisipasi PNS Perempuan dalam Jabatan Struktural. Dalam mengkaji hal tersebut penulis menggunakan tiga pendekatan yaitu Women’s Sex Role, Gender Stereotype dan Work Environment. Penulis melakukan wawancara mendalam kepada 10 Informan dari enam Instansi yang berada di Lingkungan Pemerintah Kota Medan. Kemudian untuk mengolah data yang diperoleh penulis melakukan analisis menggunakan enam tahapan dari Cresswell.Hasil penelitian menunjukan bahwa Women’s Sex Role, Gender Stereotype dan Work Environment menjadi faktor yang mempengaruhi peningkatan Jenjang Karir  Pegawai Negeri Sipil Perempuan di Lingkungan Pemerintah Kota Medan. Sehingga untuk mengatasi hal tersebut dan meningkatkan Partisipasi PNS Perempuan dalam jabatan struktural atas hal yang harus diperhatikan atau implikasi kebijakannya adalah Mendesain Infrastruktur yang sensitif terhadap gender, Meningkatkan keterlibatan perempuan dalam jabatan publik dan kebijakan dan memperbaiki Kebijakan terkait ASN dalam pelaksanaan merit system khsusunya dalam hal promosi jabatan.